Digital Entrepreneurial Readiness Among High School Students: The Roles of Digital Financial Literacy, Self-Efficacy, And Digital Creativity - Intan Rizqi Dwi Istighfarin; Norida Canda Sakti (Paedagogia: Jurnal Pendidikan, 2026)
The rapid growth of Indonesia's digital economy contrasts sharply with the low level of youth entrepreneurship, revealing a significant gap between digital access and entrepreneurial action. This study examines the integrated influence of digital financial literacy, self-efficacy, and digital creativity on digital entrepreneurial readiness among high school students, focusing on the psychological mechanisms that transform competencies into readiness. Using a quantitative approach, data were collected through structured questionnaires from 125 students in the P5 Entrepreneurship Program and analyzed using PLS-SEM. The results show that the model explains 67.8% of the variance in digital entrepreneurial readiness, with self-efficacy acting as a key mediator. Digital creativity shows the strongest effect on self-efficacy, while self-efficacy significantly influences readiness. These findings reveal that psychological mechanisms are as important as technical competencies in fostering entrepreneurial readiness. This study provides evidence-based recommendations for integrating digital skills development with psychological readiness building in Indonesia's Merdeka Curriculum, offering specific strategies for curriculum design and educational policy to bridge the digital entrepreneurship gap among youth.